Caracterización morfológica del naranjillo (Trichanthera gigantea) en el bosque húmedo de La Mana - Armas Veloz, Oscar Marcelo (2017)
The present research project was carried out ot Cotopaxi province, in the bioclimatic grounds, those are in the Evergreen Forest low and Evergreen seasonal mountain of the Western Mountain range of the Andes. It was divided into three altitudinal zones (high, medium and low), ranging from 600 m.o.s.l to 2.200 m.o.s.l The objective of the project was to perform the morphological characterization of the forest species Naranjillo (Trichanthera gigantea) by using qualitative and quantitative traits. The area was recognized on-site and with the help of a GPS, georeferenci the area, delimiting the altitudinal zones. The presence of individuals on the three altitudinal zones was identified for the verification of the distribution of the Naranjillo species, this was useful to know the population density of them. After identifying the distribution of the species, samples of the Naranjillo (Trichanthera gigantea) were collected, where 20 individuals were selected for each altitudinal zones, with a similar diameter of the stem, which allowed to obtain a characterization homogeneous. For the morphological characterization of the species, 18 qualitative descriptors were used, for a statistical analysis was performed, and 6 quantitative descriptors were used, to which a statistical analysis of data was made, an analysis of main components for searching the existence of morphological variability.